Mechanical behaviour of additively manufactured elastomeric pre-buckled honeycombs under quasi-static and impact loading. (January 2022) - Adams, Rhosslyn; Townsend, Scott; Soe, Shwe; Theobald, Peter
Graphical abstract: Highlights: Elastomeric pre-buckled circular honeycombs were additively manufactured and tested under static and dynamic loading. Variable mechanical behaviour can be achieved through informed selection of pre-buckled design feature's aspect ratio. Periodic boundary condition finite element represents a method to accurate and computationally efficient simulation. Abstract: Selective laser sintering has been used to manufacture different structural variations of a pre-buckled circular honeycomb. The mechanical behaviour of these structures has been examined under both quasi-static and dynamic impact loading. Pre-buckled circular honeycombs with aspect ratios e = 0.8 and e = 0.6 were compared to a traditional, straight-walled honeycomb. It has been found that the mechanical behaviour of the honeycomb can be tailored to yield different mechanical responses. Principally, decreasing the aspect ratio reduced the stress at yield, as well as the total energy absorbed until densification, however, this alleviated the characteristic stress-softening response of traditional honeycombs under static and dynamic conditions. When subjected to multiple cycles of loading, a stabilised response was observed. The numerical response closely agreed with the experimental results. A simplified, periodic boundary condition model also closely agreed with the experimental results whilst alleviating computational run time by nominally 75%. The numerical full factorial parameter design sweep identified a broad range of mechanical behaviour. This represents a valuable tool to identify optimal design configurations for future impact mitigating applications.